Community radio and museum outreach: a case study of community radio practices to inform the environment and sustainability programmes of Livingstone Museum - Muloongo, Arthanitius Henry (Rhodes University, Faculty of Education, Department of Education, 2011)
This is a qualitative study whose purpose was to investigate the community radio education practices and the museum outreach education activities with a view to understanding how a museum-radio partnership may be used to engage the Livingstone community in environment and sustainability learning. Environment and sustainability issues require a community approach in order to bring about sustained responses to environmental challenges. As such, the study worked with social learning ideas of engaging the community in environment and sustainability learning. The data was generated mainly from face-to-face semi-structured interviews involving three community radio stations, Radio Listener Clubs and museum experts. The data generated was then presented to a strategy workshop involving the Livingstone Museum and Radio Musi-otunya staff. Arising from this workshop, recommendations were made about the possibility of the museum working in partnership with the radio to engage the community in environmental education. The study has shown that much of the museum environmental education activities have been confined to exhibitions and lectures within the museum building, which has affected the number of people being serviced by the museum. These education activities are arranged such that museum expert-led knowledge is presented to the audience with minimal community engagement on the environmental learning content. The study has also shown that community radio programming provides opportunities for community-led social learning which the Livingstone Museum could make use of to engage the community in environmental learning. Community radio programming allows community participation through Radio Listener Clubs, in identification and presentation of local environmental issues. This makes it a suitable tool to address locally relevant environmental issues, by the local community. Environmental issues are different from one place to another. Therefore environmental education approaches that bring issues into the museum may fail to address the different environmental education issues in different community context. The study concludes by recommending that Livingstone Museum should explore the use of community radio so that their expert knowledge and that of the radio producers could be used to shape environmental education programmes to go beyond awareness-raising.
Keywords: Community radio -- Zambia; Livingstone Museum; Museum outreach programs -- Zambia; Environmental education -- Zambia